Metabolic reprogramming of breast tumor-educated macrophages revealed by NMR metabolomics - Dias, Ana S. (2023)
The metabolic crosstalk between tumor cells and tumor-associated macrophages (TAMs) has emerged as a critical contributor to tumor development and progression. In breast cancer (BC), the abundance of immune-suppressive TAMs positively correlates with poor prognosis. However, little is known about how TAMs reprogram their metabolism in the BC microenvironment. In this work, we have assessed the metabolic and phenotypic impact of incubating THP-1-derived macrophages in conditioned media (CM) from two BC cell lines cultured in normoxia/hypoxia: MDA-MB-231 cells (highly metastatic, triple-negative BC), and MCF-7 cells (less aggressive, luminal BC). The resulting tumor-educated macrophages (TEM) displayed prominent differences in their metabolic activity and composition, compared to control cells (M0), as assessed by exo- and endometabolomics. In particular, TEM turned to the utilization of extracellular pyruvate, alanine, and branched chain keto acids (BCKA), while exhibiting alterations in metabolites associated with several intracellular pathways, including polyamines catabolism (MDA-TEM), collagen degradation (mainly MCF-TEM), adenosine accumulation (mainly MDA-TEM) and lipid metabolism. Interestingly, following a second-stage incubation in fresh RPMI medium, TEM still displayed several metabolic differences compared to M0, indicating persistent reprogramming. Overall, this work provided new insights into the metabolic plasticity of TEM, revealing potentially important nutritional exchanges and immunoregulatory metabolites in the BC TME.